Experimental study on combustion and thermal characteristics of impinging premixed flames for low heating value gas (LHVG) fuels - Hyeon Taek Nam; Yuseon Jeon; Seungro Lee; Heejung Jung (Case Studies in Thermal Engineering, 2023)
The combustion and thermal characteristics of impinging premixed flames for low heating value gases (LHVGs) composed of methane, propane, and nitrogen are experimentally investigated. For the experiment, a combustor with an impingement plate is used to study the flame stability regions based on flame shapes and visualize OH radical distribution. The OH radical distribution is observed via OH* chemiluminescence and OH planar laser-induced fluorescence (OH-PLIF). Thermal characteristics are investigated by measuring the temperature distribution of the plate and the heat transfer rate into the cooling water. The results show that the flame stability region narrows as the heating value of the fuels decreases. Also, as the equivalence ratio increases (i.e., »1), the flame stability region is expanded. The OH radical intensity of LHVGs is observed to be lower than that of methane. The OH-PLIF images show where OH radicals are more distributed in the flame. The temperature distribution of the plate is determined by the flame shape according to the heating value, and the heat transfer rate into the water has a linear tendency to the fuel's thermal power. Based on these findings, LHVGs can be utilized without system improvement within the flame stability range in the impinging flame system.